The influence of organizational culture, work discipline, and communication on employee performance at PT X in Batam City - Herika Dessy Suryani; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of Organizational Culture, Work Discipline, and Communication on Employee Performance at PT X. Using a quantitative associative–causal design, data were collected from 100 employees selected through the Slovin formula. Statistical analyses, including validity and reliability tests, classical assumption tests, and multiple linear regression, were conducted using SPSS. The findings reveal that all three independent variables have a positive and significant effect on employee performance, both partially and simultaneously, with a coefficient of determination (R²) of 0.714. Among these, communication exerts the strongest influence, indicating that effective interaction and information flow are critical to achieving optimal performance. The results confirm that behavioral and relational factors remain central to organizational effectiveness, particularly in industrial settings.